Cognition‐related structure in the progression of Alzheimer's disease: Neuroimaging / Optimal neuroimaging measures for tracking disease progression. (7th December 2020) - Mao, Chenhui; Li, Jie; Huang, Xinying; Lei, Dan; Liu, Caiyan; Dong, Liling; Peng, Bin; Cui, Liying; Gao, Jing
Abstract: Background: Typical Alzheimer's disease (AD) presented with memory loss, followed by global involvement of cognitive domains in the progression of the disease. Bilateral medial temporal lobe and posterior atrophy was most common structure imaging changes. Method: 111 patients diagnosed probable AD based on 2011 NIA‐AA guideline were enrolled. All of them had systemic cognitive evaluation including MMSE, MOCA, CDR, ADL and domain specific batteries. The severity of the disease was defined by MMSE score: 1‐10 severe, 11‐20 moderate, 21‐30 mild. 3D‐T1 MRI data were analyzed using voxel based morphometry supported by DR. BRAIN platform. The volumes of bilateral hippocampus, superior temporal gyrus, superior parietal lobe, posterior cingulate gyrus as well as total grey matter and white matter were calculated. Result: The male: female ratio was 38:73. The average age was 70.8. The mild: moderate: severe ratio was 48:38:25. The volume of left hippocampus was 2127.8, 1973.2, 1757.6mm 3 in mild, moderate and severe group respectively. The volume of right hippocampus was 2426.8, 2275.9, 2101.3mm 3 . The volume of left superior temporal gyrus was 5354.9, 4888.8, 4358.1mm 3 . The volume of right superior temporal gyrus was 5690.6, 5139.5, 4872.8mm 3 . The volume of left superior parietal lobe was 8663.0, 7873.0, 7065.6mm 3 . The volume of right superior parietal lobe was 8533.1, 7858.9, 7227.1mm 3 . The volume of left posterior cingulate gyrus was 3364.7, 3028.5, 2816.3mm 3 . The volume of right posterior cingulate gyrus was 3071.3, 2779.2, 2612.0mm 3 . Atrophy of all the above area was significantly associated with progression of AD, while posterior area more prominent. The volume of total grey matter was 549373.9, 514908.9, 488812.2mm 3 . The volume of total white matter was 435153.6, 422331.1, 423894.8mm 3 . Grey matter volume was significant related to cognition while white matter not, which was in consistent with previous knowledge. Conclusion: Cognition deterioration was associated with structure atrophy in the progression of AD. Bilateral hippocampus, superior temporal gyrus, superior parietal lobe, posterior cingulate gyrus were all closely related. Besides hippocampus, we reported diffuse cortex including lateral temporal lobe and posterior areas structure change was important.